2003
DOI: 10.2337/diacare.26.6.1738
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial Comparing Breakfast, Dinner, or Bedtime Administration of Insulin Glargine in Patients With Type 1 Diabetes

Abstract: FOR THE HOE901/4007 STUDY GROUPOBJECTIVE -Insulin glargine (Lantus), a long-acting human insulin analog, provides effective glycemic control when administered at bedtime. This open-label, randomized, parallel group, multicenter study investigated whether insulin glargine is equally effective if administered before breakfast, before dinner, or at bedtime.RESEARCH DESIGN AND METHODS -Patients with type 1 diabetes on basal-bolus therapy (n ϭ 378, 18 -68 years, HbA 1c 5.5-9.8%) were treated with once-daily individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 9 publications
7
69
0
9
Order By: Relevance
“…The administration of isophane (NPH) insulin before the evening meal, or the use of soluble insulin with a meal consumed after 20.00 h, predispose to nocturnal hypoglycaemia. Therapeutic changes to diminish this risk include delaying the evening isophane insulin until bedtime, using a fast-acting insulin analogue (insulin lispro or aspart) before a late evening meal [20], or the use of a long-acting insulin analogue (insulin glargine or detemir) as the basal insulin -preferably administered in the morning [21]. The application of continuous subcutaneous insulin infusion (CSII) using an insulin pump, either continuously, or overnight [22] also minimizes the risk of nocturnal hypoglycaemia.…”
Section: Sleep and Nocturnal Hypoglycaemiamentioning
confidence: 99%
“…The administration of isophane (NPH) insulin before the evening meal, or the use of soluble insulin with a meal consumed after 20.00 h, predispose to nocturnal hypoglycaemia. Therapeutic changes to diminish this risk include delaying the evening isophane insulin until bedtime, using a fast-acting insulin analogue (insulin lispro or aspart) before a late evening meal [20], or the use of a long-acting insulin analogue (insulin glargine or detemir) as the basal insulin -preferably administered in the morning [21]. The application of continuous subcutaneous insulin infusion (CSII) using an insulin pump, either continuously, or overnight [22] also minimizes the risk of nocturnal hypoglycaemia.…”
Section: Sleep and Nocturnal Hypoglycaemiamentioning
confidence: 99%
“…However, 1 limitation to our study was bedtime dosing of glargine because a recent study suggested that morning dosing instead would further reduce hypoglycemia frequency. 31 Increased risk of frequent mild to moderate hypoglycemia in individuals with type 1 diabetes is usually associated with high blood glucose variability, low average blood glucose concentration, diabetes of long duration, low BMI, self-reported hypoglycemia unawareness, and vigorous physical activity. 32 In our patients, there was no correlation between hypoglycemia frequency and BMI and/or duration of diabetes.…”
mentioning
confidence: 99%
“…Vor allem bei morgendlicher Applikation von Insulin glargin besteht ein deutlich geringeres nächt-liches Hypoglykämierisiko [25]. In Einzelfällen kann auch eine 2-mal tägliche Gabe von Insulin glargin zum Erreichen einer stabilen Stoffwechseleinstellung erforderlich sein.…”
Section: Loga Weisen Bei Typ-1-diabetes Im Vergleich Zu Nph-insulin Lunclassified